Rola uziarnienia gleb w ocenie jakości siedlisk górskich - Lasota, Jarosław; Błońska, Ewa; Wanic, Tomasz; Zwydak, Maciej (Leśne Prace Badawcze, 2014)
The physical and chemical properties of soil are the basic features that are used in the assessment of mountain sites. The aim of this study was to produce a simple key for classifying forest sites in mountain areas using soil particle size distribution. 200 plots (standard typological space) were selected for examination, most of which are typical of the Carpathians – being dominated by flysch rock. A few plots were located in the Sudety and Tatra Mountains, which have a different surface geology, mostly metamorphic rock and granite. The study proved that soil properties (reaction, base saturation, content of base cations, organic carbon and nitrogen) are helpful in distinguishing and assigning soils to particular site types. The particle size distribution of forest mountain sites separated into different categories in terms of productivity. These results can be used to improve the classification of forest mountain sites.